Demokrasi dan Kampanye Hitam dalam Penyelenggaraan Pemilihan Umum di Indonesia (Analisis atas Black Campaign dan Negative Campaign) - Pamungkas, Aisyah Dara; Arifin, Ridwan (DIKTUM: Jurnal Syariah dan Hukum, 2019)
Indonesia is a country oriented to the democratic system. As stated in the 1945 Constitution Article 1 Paragraph (2) which states "Sovereignty is in the hands of the people and carried out according to the Constitution." 2019 is a political year. Soon the Indonesian people will hold a democratic party for the umpteenth time. The rise of Negative Campaigns and Black Campaigns is unavoidable ahead of general elections in Indonesia. The emergence of a black campaign became a reflection of the dilapidated morale of the Indonesian people today. It cannot be denied that black campaign has a very bad impact on the political education of the Indonesian people. The phenomenon that occurs is SARA participation in politics. Where we know that Indonesia has pluralism, we not only have one religion, culture, and tribe. Religious issues may be familiar to the public ahead of the 2019 presidential election, which raises some perspectives and assumptions that they are a form of religious politicization, embodiment of religious values ​​in politics, and the opinion of the khilafah government system in Indonesia. Differences of opinion must always exist amid a pluralistic society. The differences and diversity that exist in Indonesia can lead to conflict and division if not addressed wisely. Conversely, plurality can be an adhesive in society if it is able to be managed properly without uniformity. Therefore, ahead of the 2019 Presidential Election, the public is expected to be able to filter all the news obtained, whether the campaign used is included in the negative campaign or is it a black campaign? It is hoped that free and fair democratic parties can be realized in the upcoming 2019 Presidential Election, so that it can maintain harmony in the life of the nation and state. The community must be clever in digesting the information that is obtained and it is hoped that it will not be easily provoked for the integrity of the nation.